Analisis Keamanan Sambaran Petir pada Mobil Berdasarkan Hukum Gauss dan Konsep Sangkar Faraday - Bayu Renov Pujiyanto; Doddi Yuniardi (JOURNAL SAINS STUDENT RESEARCH, 2026)
Based on Gauss's Law, the metal body of a car acts as a Faraday cage that protects passengers from lightning strikes by creating a zero electric field inside the cabin. This article analyzes these protection mechanisms and safety measures within Indonesia's tropical climate using a descriptive-analytical literature review method. The analysis reveals that the metal body effectively channels external electrical currents to the outer surface and to the ground, while rubber tires provide negligible protection. Consequently, composite or convertible vehicles are less safe and require Lightning Strike Protection (LSP) technology, such as NiCVs or carbon nanotube-based coatings, to replicate the Faraday cage effect. In conclusion, a closed metal-bodied car is a safe shelter from lightning provided windows are closed tightly and passengers avoid touching interior metal parts.